Remitting Seronegative Symmetrical Synovitis with Pitting Edema Syndrome in a Chronic Hemodialysis Patient - Shunsuke Yamada; Seiya Fuyuno; Masahiro Eriguchi; Kazuhiko Tsuruya; Takanari Kitazono (Case Reports in Medicine)
A 75-year-old male who was undergoing chronic hemodialysis developed abrupt-onset pitting edema and pain in the dorsum of both hands and feet. Biochemical analysis disclosed increased C-reactive protein, and negative rheumatoid factor and antinuclear antibody. Radiological examination showed no bony erosion. Computed tomography and gallium scintigraphy revealed no active infection or neoplasms. The clinical diagnosis was remitting seronegative symmetrical synovitis with pitting edema (RS3PE) syndrome. The pitting edema and inflammatory response quickly subsided after low-dose prednisolone therapy. This case demonstrates that RS3PE syndrome could be a differential diagnosis in elderly patients undergoing dialysis who develop pitting edema and joint pain.